The teacher as a key player - Torgyik, Judit (Autonomy and Responsibility Journal of Educational Sciences, 2022)
Horizons - Continuing the reform of teacher education, edited by Ferenc Arató, was published in 2014 by the Institute of Educational Sciences of the University of Pécs.The book presents the writings of ten authors on the professional socialisation of the teacher profession, and at the same time, it is a work of the Pécs teacher training and educational sciences workshop, and the and its wider environment in recent years.